Dendrobium officinale flowers flavonoids enriched extract protects against acute ethanol-induced gastric ulcers via AMPK/PI3K signaling pathways - Zhiyu Zhang; Hualing Xie; Mohamed A. Farag; Zhenhao Li; Qingping Wu; Ping Shao (Food Science and Human Wellness)
Gastric ulcer is a widespread disease caused by various etiologies. Dendrobium officinale flowers exert several health benefits owing to their rich flavonoid content. In this study, protective effects and possible action mechanisms of D. officinale flowers’ flavonoid enriched extract (DOFF) were assessed against gastric ulcer. The result of sodium nitrite-aluminum nitrate colorimetry showed that 52.34% of the total extractive was flavonoid, and ultra-high performance liquid chromatography time of flight mass spectrometer (UPLC-Q-TOF/MS) revealed the presence of 28 components in DOFF of which 14 belonged to flavonoids. In addition, in vivo assay revealed DOFF potential in reducing the formation of ethanol-induced gastric mucosal lesions, with drop-in ulcer index from 64.33 ± 8.76 to 32.00 ± 4.47. Similar results were revealed in human gastric mucosal epithelia cells, with cells viability to increase from 27.2% to 61.6% post DOFF administration. To analyzed the protect effect of DOFF, we used Western blotting and immunofluorometric assay to revealed the expression levels of key proteins in cell pathways. The results showed that DOFF (320 μg/mL) could increase the level of oxidation marker protein (HO-1), apoptosis regulatory protein (Bcl-2) and autophagy marker (LC3β) by 50.84%, 43.85%, and 59.21% compared with ethanol-treated group respectively. Further analyzed of the mitochondrial activity and apoptosis pathway, we found that DOFF appeared to mitigate against ethanol-induced gastric mucosal injury via AMPK/mTOR/ULK1 and PI3K/AKT autophagy signaling pathways.